2017
DOI: 10.3324/haematol.2017.176073
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor burden assessed by whole-body magnetic resonance imaging in multiple myeloma patients treated with allogeneic stem cell transplantation

Abstract: Allogeneic stem cell transplantation is a therapeutic option under dispute but nonetheless chosen with increasing frequency for patients suffering from multiple myeloma in Europe. To study possible predictors of survival, 79 patients were investigated using whole-body magnetic resonance imaging to assess the visible tumor burden before and after allogeneic stem cell transplantation. Statistical analysis of clinical and imaging parameters included Cox regression models and distribution of survival time estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In fact, the presence of more than three residual focal lesions after induction and any residual focal lesions after high dose chemotherapy were significantly adverse prognostic factors. The same group was also able to show that residual lesions on conventional MRI are a negative prognostic factor, which was confirmed by other research groups, and in patients after allogeneic stem cell transplantation [19,20]. However, a comparison of whole body PET/CT and conventional spinal MRI, the latter limited due to availability of whole body MRI, by the Intergroupe Francophone du Myélome, showed that PET/CT more reliably predicted outcomes [21].…”
Section: Treatment Monitoringsupporting
confidence: 54%
“…In fact, the presence of more than three residual focal lesions after induction and any residual focal lesions after high dose chemotherapy were significantly adverse prognostic factors. The same group was also able to show that residual lesions on conventional MRI are a negative prognostic factor, which was confirmed by other research groups, and in patients after allogeneic stem cell transplantation [19,20]. However, a comparison of whole body PET/CT and conventional spinal MRI, the latter limited due to availability of whole body MRI, by the Intergroupe Francophone du Myélome, showed that PET/CT more reliably predicted outcomes [21].…”
Section: Treatment Monitoringsupporting
confidence: 54%
“…In these contexts, it would seem prudent to complement bone marrow MRD assessment with other techniques, that could detect heterogeneous bone marrow involvement or EMD. Imaging techniques such as magnetic resonance imaging (MRI) or positron emission tomography‐computed tomography (PET‐CT) have demonstrated their prognostic value for progression‐free survival (PFS) and overall survival (OS) in this framework.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, because mutations in ctDNA have an association with ctDNA level, then, we can infer the tumor burden or tumor size from gene mutations in ctDNA, and even the survival time for prognosis. The large tumor burden and high ctDNA level indicate shorter overall survival 19–21 . We found the association between gene mutations and ctDNA levels provides new insight into ctDNA study.…”
Section: Introductionmentioning
confidence: 69%